2016
DOI: 10.1177/0194599816670370
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Perioperative Lumbar Drainage following Endonasal Endoscopic Cerebrospinal Fluid Leak Repair: A Meta‐analysis

Abstract: Objective Perioperative lumbar drain (LD) use in the setting of endoscopic cerebrospinal fluid (CSF) leak repair is a well-established practice. However, recent data suggest that LDs may not provide significant benefit and may thus confer unnecessary risk. To examine this, we conducted a meta-analysis to investigate the effect of LDs on postoperative CSF leak recurrence following endoscopic repair of CSF rhinorrhea. Data Sources A comprehensive search was performed with the following databases: Ovid MEDLINE (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 42 publications
0
48
0
Order By: Relevance
“…Perioperative LD following endoscopic endonasal repair remains a controversial topic. A recent meta‐analysis by Ahmed et al . reviewed 12 studies examining the use of lumbar drains in the perioperative period following endoscopic endonasal repairs of CSF leaks of varying etiologies.…”
Section: Primary Csf Rhinorrheamentioning
confidence: 99%
See 1 more Smart Citation
“…Perioperative LD following endoscopic endonasal repair remains a controversial topic. A recent meta‐analysis by Ahmed et al . reviewed 12 studies examining the use of lumbar drains in the perioperative period following endoscopic endonasal repairs of CSF leaks of varying etiologies.…”
Section: Primary Csf Rhinorrheamentioning
confidence: 99%
“…At some centers, it is used routinely with good success, predominantly for larger high‐grade leaks, whereas in others it may be associated with a higher failure and meningitis rate . Two recent meta‐analyses and a review article failed to find benefit of perioperative lumbar drain placement in patients with pituitary adenomas and other skull‐base tumors, and 1 emphasized potential risk of major complications including meningitis and ventriculitis . However, there is also conflicting data showing that use of intraoperative LD may reduce the risk of intraoperative CSF leak .…”
Section: Intradural Tumorsmentioning
confidence: 99%
“…Complications after EESBS such as CSF leak can lead to costly readmissions and disrupt patient recovery, yet routine intraoperative practices such as the use of LDs and reconstructive techniques have not yet been standardized. Meta‐analyses have not shown any significant decrease in postoperative CSF leak when an LD was used in routine pituitary surgery . Similarly, a more recent large retrospective review showed no decrease in perioperative CSF leak rates in those patients undergoing lumbar drainage .…”
Section: Discussionmentioning
confidence: 98%
“…With changing trends toward endoscopic approaches for skull base surgery, the elective use of LD in such operations has been widely investigated . Recently, a prospective study found that elective LD placement is related to lower rate of postoperative CSF leaks in endoscopic skull base operations, whereas a meta‐analysis found no difference in the postoperative CSF leak rates or successful repair rates for endoscopic CSF leak repair with elective LD placement …”
Section: Discussionmentioning
confidence: 99%
“…6 With changing trends toward endoscopic approaches for skull base surgery, the elective use of LD in such operations has been widely investigated. 14,[16][17][18][19] Recently, a prospective study found that elective LD placement is related to lower rate of postoperative CSF leaks in endoscopic skull base operations, 20 whereas a meta-analysis found no difference in the postoperative CSF leak rates or successful repair rates for endoscopic CSF leak repair with elective LD placement. 21 Our current investigation revealed that patients who underwent elective perioperative LD insertion had a higher rate of malignancy as well as a higher rate of dural and intracranial extension of their lesions, and that they were treated more often with adjuvant therapy and had a longer postoperative hospitalization period.…”
Section: Discussionmentioning
confidence: 99%